Perception of Hearing Aid Users with Nonlinear Frequency Compression on Speech Recognition in Noisy Environment - Costa, Maristela Julio; Vaucher, Ana Valéria de Almeida; Moraes, Anaelena Bragança de; Gresele, Amanda Dal Piva (International Archives of Otorhinolaryngology, 2014)
Introduction: An alternative to ease the descending hearing losses and assist in understanding speech is the use of hearing aids with a nonlinear frequency compression algorithm. Objective: This study aims to investigate the perception of the elderly subjects about the effects of nonlinear frequency compression algorithm during the process of selection of hearing aids in noise. Patients and Method: The study included 46 elderly patients with sensorineural hearing loss of mild-to-moderate degree. The lists of sentences in Portuguese were applied and were searched the threshold sentence recognition in noise and a questionnaire was developed and applied in this study. The speech test was applied twice: using hearing aids with and without activation of nonlinear frequency compression. After each evaluation, the questionnaire was administered. Results: After obtaining the threshold sentence recognition in noise with and without activation of nonlinear frequency compression it was found that 23.91% (11 subjects) showed worse performance in the test, after the activation of this algorithm; 36.95% (17 subjects) showed no difference in the test results after the activation of nonlinear frequency compression; and 39.14% (18 subjects) showed better performance in the threshold sentence recognition in noise test after activation nonlinear frequency compression. Overall, 45.65% of participants (21) did not detect differences in speech understanding in noise when nonlinear frequency compression was activated. Conclusion: The effect of activation of the nonlinear frequency compression algorithm was not perceived by the subjects in relation to speech recognition in noise.